EFL pre-service teachers’ professional identity in the age of AI: An integrative review (2015-2025) - Zhu, Mian; Supyan Hussin; Harwati Hashim (Environment and Social Psychology, 2025)
The rapid integration of artificial intelligence (AI) into education is transforming how teachers are prepared and how their professional identities evolve within digitally mediated environments. While prior studies have examined AI’s influence on teaching effectiveness and digital competence, comparatively little attention has been given to its impact on the identity formation of English as a Foreign Language (EFL) pre-service teachers. This integrative review therefore aims to provide a consolidated understanding of how AI shapes their emerging teacher identities. It synthesizes 31 empirical studies published between 2015 and 2025 from Scopus and Web of Science, following PRISMA-guided screening and MMAT quality appraisal. A mixed analytical strategy combining quantitative trend mapping and qualitative thematic synthesis was employed to trace how AI use interacts with self-efficacy, reflective practice, professional agency, and ethical reasoning in teacher education. The findings indicate three interconnected roles of AI in the development of professional identity: (1) as a reflective partner that enhances metacognitive awareness through adaptive and dialogic feedback; (2) as a pedagogical scaffold that improves efficacy, motivation, and agency during lesson design and microteaching; and (3) as an ethical mediator that encourages reflection on authenticity, authorship, and moral responsibility. Across contexts, AI integration strengthens professional identity when embedded within human-centered, ethically framed pedagogies that balance automation with reflective judgment. The review concludes by proposing an AI-enhanced identity ecology and outlining implications for reflective pedagogy, ethical AI literacy, and identity-oriented teacher education, along with directions for future longitudinal and cross-cultural research.